Examination of Maternal Assets and Breast Milk Expression - K. Bai Yeon; M. Dinour Lauren (Journal of Breastfeeding Biology, 2019)
The proportion of mothers in the workforce has increased over the past 40 years. Examination of factors associated with a working/student mother’s milk expression is needed to provide effective lactation support. The purpose of this study was to examine the role of maternal assets in the relationships between the theory constructs, intention, and behavior of breast milk expression. Using a cross-sectional design framed under the theory of planned behavior, all female personnel associated with a higher education institute in northern New Jersey were invited to participate in the online survey, Milk Expression on Campus. Attitude toward breast milk expression, subjective norm, perceived behavioral control, intention, and behavior of breast milk expression on campus as well as maternal assets such as income, education, living status, and campus role were measured. Maternal assets had no moderation role but showed a significant and meaningful mediation effect on the relationship between perceived behavioral control and the intention to express breast milk on campus, with effect size R2=3.59%, 95% CI (-.1061, -.0047). There was no mediation effect of the asset on the relationship between intention and the behavior of breast milk expression, 95% CI (-.0984, .0232). Future breastfeeding support and promotion may direct its attention to provide systematic social and clinical support to enhance working/student maternal assets, e.g. family education, access to lactation services, or peer-based support programs, thereby helping mothers achieve their breastfeeding goals.
Keywords: Breastfeeding